From anthropological transfer to children’s emotional health through motor stories - Aznar-Cebamanos, Mónica; García-Barrios, Alberto; Royo-Ortín, Emilio; Peñarrubia-Lozano, Carlos; Whyte-Orozco, Jaime; Cisneros-Gimeno, Ana Isabel (Frontiers in Education, 2025)
Anthropology, in its various branches, explores human evolution and behavior in both biological and social contexts. The development of the prefrontal cortex, which occurs significantly during childhood and adolescence, is closely linked to the formation of executive functions and the establishment of the basis for future behavior. In this context, the social and educational environment, ranging from family to school, plays a crucial role in shaping the aspirations and vocations of young people. Reading, especially in the early stages of development, presents itself as a powerful tool that can foster interest in science and medicine. This article explores how the interaction between physical anthropology, child cognitive development, and literature can contribute to cultivating scientific vocations through children’s narratives. The aim of this research is to encourage medical vocation in children, combining reading and physical anthropology by introducing historical characters, such as the “Roman legionaries” who inhabited Caesaraugusta (Zaragoza, Spain) in the 2nd century A.D., through a motor story aimed at schoolchildren. This approach is used as a scientific transfer tool to generate greater interest in the medical and anthropological field among children. As a result of this proposal, a book entitled “Maripi: the scientific gladiator” has been created and edited, which will be implemented in the early childhood education classroom after its publication. This book will not only narrate the experiences and the context of the Roman legionaries, but it is also designed to capture the attention of children and stimulate their curiosity about medicine. From this work it is concluded that reading at early ages can be a facilitating element for science, in this case physical anthropology, to contribute to enhance medical vocations in the youngest and also as a resource for transferring scientific knowledge to the youngest.